1993
DOI: 10.1111/j.1460-2466.1993.tb01285.x
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of Systems: The Third Stage of the Information Society

Abstract: Postmodernism and information economics, mass communications and telecommunications, popular culture and managerial theory. Until now, they have been treated separately. Each offers a conception o f the information society that is distinguished by disciplinary history and unit of analysis, yet each is like the others in addressing issues of social change stimulated by technological development and dependent upon the global information infrastructure, and in identifying dispersal of individuating subjects (whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 2 publications
0
14
0
3
Order By: Relevance
“…They further argued that the power relation between media and users is changing and this can be viewed as more of manipulation than domination. Braman (1993) and Noam (1993) forwarded a somewhat similar argument by observing that media control has shifted from centralized monopolistic authority to a networked system connecting a wide range of media and social systems. From an economic perspective, Braman called for study of macroand microstructural forces with respect to each other and as part of a network.…”
Section: Study Analyzed the Trends In References Made To Various Theomentioning
confidence: 86%
See 3 more Smart Citations
“…They further argued that the power relation between media and users is changing and this can be viewed as more of manipulation than domination. Braman (1993) and Noam (1993) forwarded a somewhat similar argument by observing that media control has shifted from centralized monopolistic authority to a networked system connecting a wide range of media and social systems. From an economic perspective, Braman called for study of macroand microstructural forces with respect to each other and as part of a network.…”
Section: Study Analyzed the Trends In References Made To Various Theomentioning
confidence: 86%
“…This observation, combined with the input from a wider range of communication scholars in the field (i.e., established scholars ones and new entrants), brought perspectives rooted in either the evaluations of media of the past or examinations of new media environments. Through this discourse, scholars the acknowledged the interconnected new media and social environment and realized the need for more integrative, cross-level, multiprocess approaches towards studying communication (Babrow, 1993;Beniger, 1993;Braman, 1993;Lang & Lang, 1993;Noam, 1993;Rogers & Chaffee, 1993). Lang & Lang (1993) noted the field's connections to humanities, social sciences, and other professional fields and observed this connection was a part of the field's identity.…”
Section: Study Analyzed the Trends In References Made To Various Theomentioning
confidence: 95%
See 2 more Smart Citations
“…Media scholars, Nulens (2003) & Jensen (2003 state that in education, ICTs holds the promise of transforming learning in new and powerful ways with the internet playing a very prominent role. Also, Stevenson (1988), Braman (1993) and Tettey (2001) noted that ICT is the infrastructure that brings people together in different places and time zones, with multimedia tools for data, information, communication and knowledge management in order to expand the range of human capabilities. Various studies have shown that there is a global trend towards quality education for all.…”
Section: Ict's Role In Educationmentioning
confidence: 99%